Analysis of the Urgency Career Guidance and Counseling in Junior High Schools - Abdul Halim Ade; A Muri Yusuf; Afdal Afdal (Jurnal Neo Konseling, 2021)
One of the goals providing education in junior high schools is to prepare graduates to continue their studies, namely whether the education level is high school (SMA) or other equivalent level. In this case, students often experience difficulties because they are faced with various choices, whether to continue their studies to the SMA or SMK level, or students prefer to attend training to directly enter the world of work, and students even choose not to continue their studies. This article discusses the analysis of the urgency of career guidance and counseling in junior high schools. The research method used is library analysis (library research). This article describes the analysis of scientific journals that are relevant to the selected discussion. The materials discussed in this article are 1) Definition of Career Guidance and Counseling, 2) Characteristics of Middle School Career Development, 3) Goals of Career Counseling at Junior High School Level, 4) Career Counseling Techniques/Activities. From this analysis, it can be can be explained guidance and counseling is one of the services that is needed by students who are in junior high school. With existence career guidance and counseling at the junior high school level, it can Upgrade the quality of human and their prosperity.